Formulasi Dan Uji Aktivitas Antibakteri Facial Foam Minyak Biji Jintan Hitam (Nigella Sativa Oil) - Nesa Agistia; Gressy Novita; Nofriyanti Nofriyanti (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2023)
Acne is a disease that most people suffer especially among adolescent, one of the causes of acne is usually caused by the growth of acne-causing bacteria that is Staphylococcus epidermidis. One of the ingredients that can be used as an antibacterial product is black cumin seed oil (Nigella sativa oil), it is known that black cumin seed oil contains Thymoquinone and Î±-pinen which are efficacious as antibacterial. This research aims to produce a cosmetic preparation in the form of a face wash that effectively cleans the skin from dust and dirt from makeup, as well as preparations that have antibacterial activity against Staphylococcus epidermidis by using the well diffusion method. Black cumin seed oil is formulated into facial foam in several concentrations, namely 3% (FI), 5% (FII) and 7% (FIII). Evaluation of fa cial foam preparations includes examination of organoleptic, pH, foam power, skin irritation, homogeneity, wetting power, alcohol insoluble portion, freeze and thaw, examination of mineral oil, washability and antibacterial activity. Data analysis using One Way ANOVA statistical test and descriptive. The result showed that the physical stability test, the three facial foam formulas have good physical stability and meet the pH requirements of topical cosmetic preparation. In the antibacterial activity test, it was found that the facial foam preparation of black cumin seed oil give inhibition of 15.37 mm (FI), 16.52 mm (FII) and 17.25 mm (FIII). Based on the one way ANOVA statistical data, the p value <0,05 which means that three is a significant difference in inhibition diameter between FI, FII and FIII which negative control and positive control. It is concluded that the facial foam preparations of black cumin seed oil was physically stable and based on antibacterial activity tests, it is known that FIII has the most bacterial resistance of 17.25 mm with medium resistance category.